Bystander T cell activation--implications for HIV infection and other diseases. - Bangs, S; Mcmichael, A; Xu, X (2006)
T cells are subject to tight regulatory measures, as uncontrolled responses might be detrimental to the host. Control measures include central or thymic tolerance, and peripheral tolerance mechanisms acting after naive T cells have encountered their cognate antigen, such as anergy induction, the contraction phase (whereby the majority of the expanded effector population undergoes apoptosis), and the action of regulatory T (Treg) cells. However, bystander T-cell activation circumvents the requirement for specific T-cell receptor stimulation, enabling T cells to bypass certain control checkpoints. The physiological relevance of the phenomenon is the subject of much controversy. This article argues that although of little consequence in the healthy individual, bystander activation could have a devastating impact in the context of disease. We focus on HIV and infection-triggered autoimmune disease as examples.